Fakultas Psikologi Universitas 17 Agustus 1945 - Veny Iswantiningtyas; Amanda Rr. Pascarini (Jurnal Psikologi Tabularasa, 2012)
Abstract Relationship of democratic parenting, creativity and Advertsity Quotient examined on 101 boys and 131 girls, 13 to 16 years of ages, and living with biologic parents. Data obtained from to scales of C.O.R.E, CO2RE and P and analyzed with regression. Democratic parenting are highly significant predict creativity; Democratc parenting are highly significant predict Adversity Quotient total scores; No relationship between democratic parenting with sub scales of Control and Endurance; Positive relationship and significant between democratic discussed in term of their implications for middle adolescent in context. Keywords: Democratic Parenting, Creativity, Adversity Quotient.